(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Permanent magnet synchronous motor (PMSM) uses the permanent magnet in the rotor for excitation. Its high efficiency and controllable power factor make it suitable for electric vehicles and other applications requiring high performance. Numerous studies have explored control strategies for PMSM, and sensorless control in PMSM eliminates the need for a position sensor, thereby reducing system complexity. However, sensorless control systems based on position error are prone to significant transient errors during the speed ramp stage. Typically, with a third-order actual position at a given ramp speed, the traditional type-II quadrature PLL (QPLL) is unable to estimate the position without incurring static error. This paper proposes an improved type III phase-locked loop (IPLL), which can effectively reduce this error, easier parameters tuning, and be suitable for all sensorless control based on position error. A detailed theoretical analysis and simulation comparison of sensorless systems based on QPLL and IPLL are presented. Simulation results verified that the proposed IPLL has stronger suppression ability to error and can limit the maximum position error to less than 3°, resulting in stronger load-carrying performance.